Domperidone and sudden cardiac death in the elderly due to ventricular arrhythmias in developing countries - Azeen Razzaq; Shafaq Saleem; Hassan Javed (Journal of the Pakistan Medical Association, 2024)
To the Editor, Domperidone is a prokinetic drug used to treat many gastrointestinal conditions including delayed gastric emptying and gastroesophageal reflux disease due to its promotility effects by antagonism on dopamine-2 receptors in the gut. It has also been used as an over-the-counter drug for nausea and vomiting due to its direct action on the chemoreceptor trigger zone involved in vomiting. The drug has gained a lot of popularity as it is more effective than other prokinetic drugs like mosapride and metoclopramide. In addition, it causes less drowsiness than metoclopramide and mosapride because it does not readily cross the blood-brain barrier(1). However, this drug has many side effects including dry mouth, headache and weight gain(2). Despite this, domperidone has been used as a prokinetic in many countries for a long time. However, the more critical concern about the use of domperidone is QT interval prolongation and its association with sudden cardiac death due to ventricular arrhythmias in patients aged 50 years and older and in those taking more than 30mg/day. A meta-analysis conducted in November 2018 by Bor et al. compared the odds of developing cardiovascular events like sudden cardiac death in patients aged >50 taking domperidone more than 30mg/day to patients not taking domperidone or any other drugs was consistent with statistically significant increased risk of sudden cardiac deaths due to ventricular arrhythmias (OR: 2.09, 95% CI, 1.59 to 2.75, p<0.001)(3). These are not the only studies to show these results. Many other studies have been done so far which showed an association between domperidone usage and sudden cardiac deaths in the elderly. A systematic review published in 2021 pooled data across multiple studies and showed that domperidone was significantly associated with an increased risk of sudden cardiac death and ventricular arrhythmias in older patients when taken more than 30mg/day. In this meta-analysis when data were pooled across nonoverlapping multiple studies, domperidone was associated with an increased risk of sudden cardiac death in the elderly compared to non-use (adjusted odds ratio: 1.69(1.46-1.95)(4). As far as the young population is concerned, there are very few studies done, so more research needs to be done to find out if domperidone causes sudden cardiac death in young patients. Despite all these concerns, this drug is still being prescribed in many developing countries, especially in Pakistan. —Continue